2022
DOI: 10.1159/000521833
|View full text |Cite
|
Sign up to set email alerts
|

Serum Potassium Disorders Predict Subsequent Kidney Injury: A Retrospective Observational Cohort Study of Hospitalized Patients

Abstract: Introduction Electrolytes disorders are common findings in kidney diseases and might represent a useful biomarker preceding kidney injury. Serum potassium [K+] imbalance is still poorly investigated for association with acute kidney injury (AKI) and most evidence come from intensive care units (ICU). The aim of our study was to comprehensively investigate this association in a large, unselected cohort of hospitalized patients. Methods: We performed a retrospective observational cohort study on the inpatient po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It was also suggested that high potassium concentrations are associated with the development, progression, and prognosis of AKI [28,30] . Potassium levels in our study were greater among dialyzed patients than among improved patients, which is consistent with the findings of Chen et al [28] , who reported an association between high potassium levels and poor prognosis among ICU patients with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that high potassium concentrations are associated with the development, progression, and prognosis of AKI [28,30] . Potassium levels in our study were greater among dialyzed patients than among improved patients, which is consistent with the findings of Chen et al [28] , who reported an association between high potassium levels and poor prognosis among ICU patients with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Lombardi et al [ 32 ] published a retrospective, observational trial (cohort study), that included in-hospital treated patients (January 2010 until December 2014, Fondazione Policlinico Universitario A. Gemelli IRCCS). The study design was interesting in so far, that all patients finally included in the analysis had not developed AKI during an initial period of 10 days.…”
Section: Methodsmentioning
confidence: 99%